Reduced graphene oxide-mesoporous carbon nitride as photocatalyst for removal of N-nitrosopyrrolidine - Tiong, Peggy (2015)
The fast electron-hole recombination in mesoporous carbon nitride (MCN) photocatalyst has spurred a great interest to improve its efficiency with addition of various modifiers. In the present study, the MCN was modified by reduced graphene oxide (rGO) that was synthesized via a novel photocatalytic reduction method with different ratios of GO to MCN to produce rGO-MCN composites. The synthesized rGO-MCN samples were characterized by X-ray diffractometer (XRD), diffuse reflectance UV-visible (DR UV-Vis), and Fourier transform infrared (FTIR) spectroscopies. It was confirmed that rGO was successfully combined with the MCN without affecting the structure of the MCN. With the higher amount of GO ratio, the composites showed more observable rGO peaks in the IR spectra and higher background absorption in the visible region of DR UV-Vis spectra. The photocatalytic removal of N-nitrosopyrrolidine (NPYR) was carried out at room temperature under visible light irradiation to investigate the photocatalytic efficiency of the composites. The ratio of GO was found to affect the photocatalytic activity of the rGO-MCN composites. The photocatalytic activity of the prepared composites increased with GO loading from 1 to 5 wt.%, owing to the slightly enhanced absorption in visible light as shown in DR UV-Vis spectra and the undisrupted graphitic structure of MCN upon characterizations by XRD and IR spectra. It was found that 5 wt.% was the optimum amount of GO ratio and there was no further improvement in photocatalytic activity when the GO ratio increased.